2010
DOI: 10.1603/en09127
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Distribution and Abundance of Soybean Aphid in Soybean Fields Using Measurements From the Surrounding Landscape

Abstract: Soybean aphid (Aphis glycines Matsumura) is a severe pest of soybean in central North America. Outbreaks of the aphid in Ontario are often spotty in distribution, with some geographical areas affected severely and others with few or no aphid populations occurring in soybean for the duration of the season. A. glycines spend summers on soybean and overwinter on buckthorn, a shrub that is widespread in southern Ontario and is commonly found in agricultural hedgerows and at the margins of woodlots. A. glycines lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…Soybean fields should be scouted on a regular basis because soybean aphid populations can increase rapidly (Hodgson et al 2012;McCornack et al 2004;Ragsdale et al 2007), particularly when winged aphids migrate within and between fields (Costamagna et al 2013). Early-season (i.e., May through mid-July) scouting should focus on fields that have histories of early colonization by soybean aphids, particularly early-planted fields and fields near buckthorn, Rhamnus spp., the overwintering host of soybean aphid (Bahlai et al 2010). More fields should be scouted as soybean aphid populations develop throughout the growing season and plants begin to enter reproductive (R) stages.…”
Section: Biological and Economic Considerations In Soybean Aphid Manamentioning
confidence: 99%
“…Soybean fields should be scouted on a regular basis because soybean aphid populations can increase rapidly (Hodgson et al 2012;McCornack et al 2004;Ragsdale et al 2007), particularly when winged aphids migrate within and between fields (Costamagna et al 2013). Early-season (i.e., May through mid-July) scouting should focus on fields that have histories of early colonization by soybean aphids, particularly early-planted fields and fields near buckthorn, Rhamnus spp., the overwintering host of soybean aphid (Bahlai et al 2010). More fields should be scouted as soybean aphid populations develop throughout the growing season and plants begin to enter reproductive (R) stages.…”
Section: Biological and Economic Considerations In Soybean Aphid Manamentioning
confidence: 99%
“…Of the aphids that remain on buckthorn, alates are eventually formed, perhaps by a density dependant mechanism , and migrate to soybean fields. The colonization of soybean from buckthorn remains complicated in both the timing and the influence of landscape, particularly the proximity to buckthorn Bahlai et al 2010). Ragsdale et al (2004) noted that colonization occurred in only 4 of 42 locations of soybean aphid infested buckthorn stands that contained potted soybean plants.…”
Section: Population Biology Issues: the Distribution And Spread Of Bimentioning
confidence: 99%
“…Random mortality during the spring colonization of soybean suggests that colonization of soybean may be restricted or most important at small spatial scales, dependant on buckthorn abundance and proximity. Using population dynamic modeling and the Akaike's information criterion (which compares the likelihood of competing models), Bahlai et al (2010) showed that, indeed, the presence or absence of buckthorn was highly related to soybean aphid colonization, and the estimated number of buckthorn shrubs best predicted aphid density, although the distances explored were less than 5km. As soybean aphids likely use both short and long distance dispersal (Zhang et al 2008;Michel et al 2009) expanding these models across larger distances would improve the ability of identifying buckthorn source populations for soybean colonization.…”
Section: Population Biology Issues: the Distribution And Spread Of Bimentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2003 soybean aphid outbreak in Iowa it has been estimated that more than a quarter of a billion dollars was lost due to lost yield and spraying costs (Pilcher et al, 2005). A study by Bahlai et al, (2010) found that the ratio of buckthorn density to field area was the most important factor for predicting the early-season density of soybean aphids. Buckthorn is considered to be an important source for oat crown rust spores in temperate areas (Heimpel et al, 2010;United States Department of Agriculture, 2008).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%